2017
DOI: 10.1007/s00228-017-2295-2
|View full text |Cite
|
Sign up to set email alerts
|

Impact of glutathione transferases genes polymorphisms in nevirapine adverse reactions: a possible role for GSTM1 in SJS/TEN susceptibility

Abstract: We observed an association between GSTM1 and SJS/TEN susceptibility. Moreover, GSTM1 contributes to the definition of a genetic risk profile for SJS/TEN susceptibility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 40 publications
0
16
0
Order By: Relevance
“…It was reported that the GSTM1-null and GSTT1-null were associated with the risk of hepatotoxicity in HIV positive patients [17]. In addition, significant association of GSTM1-null with the development of Stevens-Johnson syndrome and toxic epidermal necrolysis has been reported in HIV patients in Mozambique [16]. Therefore, identification of these genes in our antiretroviral-prescribed patients could facilitate the determination of higher-risk groups.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…It was reported that the GSTM1-null and GSTT1-null were associated with the risk of hepatotoxicity in HIV positive patients [17]. In addition, significant association of GSTM1-null with the development of Stevens-Johnson syndrome and toxic epidermal necrolysis has been reported in HIV patients in Mozambique [16]. Therefore, identification of these genes in our antiretroviral-prescribed patients could facilitate the determination of higher-risk groups.…”
Section: Discussionmentioning
confidence: 90%
“…GSTM1, GSTT1 and GSTP1 are located on chromosome 1p13.3; 22q11.2 and 11q13.2 respectively [8,9]. Deletions of GSTM1 and GSTT1 genes as well as the polymorphism c.313A > G (rs1695) in GSTP1 have been associated not only with risk of developing certain multifactorial diseases such as cancer [10], diabetes [11], arterial hypertension [12], inflammatory bowel disease [13], hepatocellular carcinoma [14], but also therapeutic outcomes such as non-small cell lung cancer [15] and AIDS [16,17]. Recently, the G allele of GSTP1 was found to be associated with better performance in Russian athletes [18].…”
Section: Introductionmentioning
confidence: 99%
“…The search strategy generated 1208 citations, of which 136 appeared to be relevant to the systematic review. Of these 136 studies, 31 were excluded, leaving 105 studies eligible for the systematic review (Figure and Table ). Among the 105 studies (5554 cases and 123 548 controls) included in the systematic review on genetic predictors potentially associated with T cell–mediated hypersensitivity to drugs, 52 were related to carbamazepine (CBZ) (n = 31) (Table ) or other aromatic antiepileptic drugs (n = 24, three studies also addressed CBZ) (Table ) .…”
Section: Resultsmentioning
confidence: 99%
“…Singh et al, (2017) showed that GSTT1-null and GSTM1-null genotypes alone and in combination may predict the acquisition of hepatotoxicity, so disease progression [36]. Ciccacci et al, (2017) shown that only GSTM1-null was associated to HIV disease progression [37]. Kuleape et al, (2018) found that double deletion of glutathione S-transferase M1 and T1 is statistically associated with normal CD4+ count in Ghanaians patients diagnosed with HIV/ AIDS [38].…”
Section: Discussionmentioning
confidence: 99%